Pelatihan Maintenance Korosi Pada Baling Baling Kapal Klotok Balikpapan-Penajam Pasir Utara (PPU) - Suherna Suherna; Patunru Patunru; Yuliana Simons (Abdimas Universal, 2019)
Community service is one of the tri dharma of higher education which is the duty of lectures college students, therefore in this servicewe rised the issue of how to maintain corrosion on klotok ship propellers for the Balikpapan-PPU routeand how to conduct optimal training activities so that theactors, owners and operators are orderly and take good care. The method of implementation is the form of training for 2 days and mentoring for 3 consecutive months. This training activity involved 2 lectures and 3 college students. This ship propeller maintenance training was attendedby 30 people consisting of 10 ship owners and 20 klotok ship operators. Implementation of on august 31st – September 1st 2018 with the hope that the owners and operators of the klotok ships can understand the importance of their klotok care so thath people who use sea transportation, especially the people of Balikpapan and Penajam Pasir Utara feel safe and confortable while in the klotok ship. This training makes it easier for ship owners to monitor operators directly and carryng our their klotok and operators also do not arbitrarily runklotok without maintenance. Keywords: klotok ships, maintenance, ship propellers, ship operators, training.